Open source systems : integrating communities : 12th IFIP WG 2.13 International Conference, OSS 2016, Gothenburg, Sweden, May 30-June 2, 2016, Proceedings /: integrating communities : 12th IFIP WG 2.13 International Conference, OSS 2016, Gothenburg, Sweden, May 30-June 2, 2016, Proceedings. (2016) - Unknown
No abstract available